Expressive Voting and Its Cost: Evidence From Runoffs With Two or Three Candidates - Pons, Vincent; Tricaud, Clémence (Econometrica, 2018)
In French parliamentary and local elections, candidates ranked first and second in the first round automatically qualify for the second round, while a third candidate qualifies only when selected by more than 12.5 percent of registered citizens. Using a fuzzy RDD around this threshold, we find that the third candidate's presence substantially increases the share of registered citizens who vote for any candidate and reduces the vote share of the top two candidates. It disproportionately harms the candidate ideologically closest to the third and causes her defeat in one fifth of the races. Additional evidence suggests that these results are driven by voters who value voting expressively over voting strategically for the top‐two candidate they dislike the least to ensure her victory; and by third candidates who, absent party‐level agreements leading to their dropping out, value the benefits associated with competing in the second round more than influencing its outcome.